Assessment of planning performance in clinical samples: Reliability and validity of the Tower of London task (TOL-F). (August 2015) - Köstering, Lena; Schmidt, Charlotte S.M.; Egger, Karl; Amtage, Florian; Peter, Jessica; Klöppel, Stefan; Beume, Lena-A.; Hoeren, Markus; Weiller, Cornelius; Kaller, Christoph P.
Abstract: Objective: Executive deficits are frequent sequelae of neurological and psychiatric disorders, but their adequate neuropsychological assessment is still a matter of contention, given that executive tasks draw on a multitude of cognitive processes that are often not sufficiently specified. In line with this, results on psychometric properties of the Tower of London, a task measuring planning ability as a prototypical executive function, are equivocal and furthermore lacking completely for adult clinical populations. Methods: We used a structurally balanced item set implemented in the Tower of London (Freiburg version, TOL-F) that accounts for major determinants of problem difficulty beyond the commonly used minimum number of moves to solution. Split-half reliability, internal consistency, and criterion-related concurrent validity of TOL-F accuracy were assessed in patients with stroke ( N =60), Parkinson syndrome ( N =51), and mild cognitive impairment ( N =29), and healthy adults ( N =155). Results: Across samples, mean split-half and lower-bound indices of reliability of accuracy scores were adequate ( r ≥.7) or higher. Compared to a subset of healthy controls matched for age, sex, and education levels, deficits in planning accuracy emerged for all three clinical samples. Conclusions: Based on consistently adequate reliability and a good criterion-related validity of accuracy scores, the TOL-F demonstrates its utility for testing planning ability in clinical samples and healthy adults. Using item sets systematically accounting for several determinants of task difficulty can thus significantly enhance the contended reliability of executive tasks and provide an opportunity to resolve the underspecification of cognitive processes contributing to executive functioning in health and disease. Highlights: Assessment of planning ability in Stroke, Parkinson, and Mild Cognitive Impairment. A version of the Tower of London task with a structurally balanced item set is used. For all groups split-half and lower-bound reliability indices are adequate or high. Patients' performance is consistently worse than that of well-matched controls The reliability and criterion validity of a complex cognitive task is demonstrated.